Pemilihan Tuhan Berdasarkan Hati bukan Penampilan berdasarkan Kajian Historis-Kritis I Samuel 16:1-13 (International Forum of Researchers and Lecturers, 2024)
This article examines the story of David’s election as king of Israel in 1 Samuel 16:1-13 through a historical-critical approach. The focus of this study is to understand how God chooses based on the heart, not the outward appearance, as emphasized in verse 7. This study highlights the differences between how humans and God judge a person, as well as the importance of inner qualities in choosing a leader. Through this analysis, it is found that God asserts His sovereignty and prioritizes faithfulness, humility, and obedience as the main criteria in determining the leader of His people. This story is theologically and practically relevant to today’s life, especially in character development and spiritual leadership.